Perspectives on Platform Regulation Concepts and Models of Social Media Governance | Across the Globe - Bayer, Judit; Holznagel, Bernd; Korpisaari, Päivi; Woods, Lorna (Recht und Digitalisierung | Digitization and the Law, 2021)
Online social media platforms set the agenda and structure for public and private communication in our age. Their influence and power is beyond any traditional media empire. Their legal regulation is a pressing challenge, but currently, they are mainly governed by economic pressures. There are now diverse legislative attempts to regulate platforms in various parts of the world. The European Union and most of its Member States have historically relied on soft law, but are now looking to introduce regulation. Leading researchers of the field analyse the hard questions and the responses given by various states. The book offers legislative solutions from various parts of the world, compares regulatory concepts and assesses the use of algorithms.